Genetic and epigenetic analysis of the beta-2-microglobulin gene in microsatellite instable colorectal cancer - Snahnicanova, Zuzana; Kasubova, Ivana; Kalman, Michal; Grendar, Marian; Mikolajcik, Peter; Gabonová, Eva; Laca, Ludovit; Caprnda, Martin; Rodrigo, Luis; Ciccocioppo, Rachele; Kruzliak, Peter; Plank, Lukas; et al. (Clinical and Experimental Medicine, 2020)
One of the most common mechanisms of immune evasion in MSI colorectal cancers (CRCs) is loss of HLA class I expression due to mutations in B2M gene which can become a negative predictor for checkpoint blockade therapy. The aim of this study was the determination of prevalence of B2M somatic mutations in MSI CRC patients and relationship between B2M mutations and lymphocytes infiltration and other clinicopathological features as well as detection of methylation changes in B2M promoter region which can be another mechanism of immune escape. In our study, 37 MSI-H and 5 MSI-L patients were selected for screening of B2M mutational and methylation status. The characterization of patients was based on standard histopathological diagnosis and TNM classification; BRAF, KRAS mutations, tumor-infiltrating lymphocytes and peritumoral lymphoid reaction were also determined. MSI analysis was performed using fragment analysis. B2M mutations were identified by Sanger sequencing, and methylation of CpG islands in promoter region was detected by methylation-specific PCR. Heterozygous mutations in the B2M gene were detected in five MSI-H patients (13.5%), while the mutation c.45_48delTTCT was determined in four patients and mutation c.276delC was found in two patients. One of these five patients was compound heterozygote harboring both mutations. Methylation of the promoter region of the B2M gene was observed in one patient with MSI-H colorectal cancer. Detection of genetic and epigenetic changes in B2M gene could be important in personalized therapy for CRC patients as these changes may be one of the mechanisms of secondary resistance of MSI positive tumors to immunotherapy.
Keywords: mutace; regulace genové exprese u nádorů; dospělí; kolorektální nádory; Female; mikrosatelitní nestabilita; CpG ostrůvky; Adult; ženské pohlaví; Gene Expression Regulation, Neoplastic; Colorectal Neoplasms; lidé; staging nádorů; Mutation; beta-2-mikroglobulin; Aged, 80 and over; metylace DNA; Microsatellite Instability; beta 2-Microglobulin; epigeneze genetická; CpG Islands; Down-Regulation; Male; Aged; DNA Methylation; lidé středního věku; senioři nad 80 let; down regulace; senioři; mužské pohlaví; promotorové oblasti (genetika); Promoter Regions, Genetic; Middle Aged; Neoplasm Staging; Epigenesis, Genetic; Humans